TRUST AND RELATIONAL COMMITMENT IN REVIEW IN HIGHER EDUCATION MARKETING (Studies in the University High School Darul Ulum (Unipdu) Jombang) - Maryati, Wiwik (Entrepreneur, 2011)
AbstractThe success of the service organization for long term efforts encourage to be accepted the relationship marketing, the trust and the commitment role become the key factor in marketing. Unipdu is the service organization that provides the high education level. In this regard, the interesting phenomena to be searched is how far Unipdu can responds students trust by increasing relationship marketing for upgrading cognitive and emotional trust in order to get the commitment from university students. The purposes of this research are: 1. analyze the effects of cognitive trust for the emotional trust and analyze the effects of cognitive and emotional trust for commitment.This research is done by taking the sample of the last S1 degree program students of Unipdu Jombang who are attacking the thesis guidance. The main instrument is collecting the data by the questionnaire forms and it’s measured with likert scale with the data analysis method that used is regresion analysis. Finally, the cognitive trust has the positive effects and significant to the emotional trust. Cognitive and emotional trust has the positive effects and significant to the commitment.Key Words: cognitive trust, emotional trust, commitment, relationship marketingAbstrakKeberhasilan organisasi layanan untuk upaya jangka panjang mendorong untuk diterima pemasaran hubungan, kepercayaan dan peran komitmen menjadi faktor kunci dalam pemasaran. Unipdu adalah organisasi layanan yang menyediakan tingkat pendidikan tinggi. Dalam hal ini, fenomena menarik untuk ditelusuri adalah seberapa jauh Unipdu dapat merespon kepercayaan siswa dengan meningkatkan hubungan pemasaran untuk meningkatkan kepercayaan kognitif dan emosional untuk mendapatkan komitmen dari mahasiswa. Tujuan dari penelitian ini adalah: 1. menganalisis efek kognitif kepercayaan atas kepercayaan emosional dan menganalisis pengaruh kepercayaan kognitif dan emosional untuk penelitian commitment.This dilakukan dengan mengambil sampel dari S1 Program siswa terakhir dari Unipdu Jombang yang menyerang bimbingan tesis. Instrumen utama pengumpulan data dengan kuesioner dan bentuk-bentuk itu diukur dengan skala likert dengan metode analisis data yang digunakan adalah analisis regresi. Akhirnya, kepercayaan kognitif memiliki efek positif dan signifikan terhadap kepercayaan emosional. Kepercayaan kognitif dan emosional memiliki efek positif dan signifikan terhadap komitmen.Kata Kunci: kognitif kepercayaan, kepercayaan emosional, komitmen, pemasaran hubungan